Preterm birth among African American and white women: a multilevel analysis of socioeconomic characteristics and cigarette smoking. Issue 8 (25th July 2003) - Ahern, J; Pickett, K E; Selvin, S; Abrams, B
Abstract : Study objective: Research shows that neighbourhood socioeconomic factors are associated with preterm delivery. This study examined whether cigarette smoking and individual socioeconomic factors modify the effects of neighbourhood factors on preterm delivery. Design: Case-control study. Setting: Moffit Hospital in San Francisco, California. Participants: 417 African American and 1244 white women, including all preterm and a random selection of term deliveries 1980–1990, excluding non-singleton pregnancies, congenital anomolies, induced deliveries, and women transported for special care. US census data from 1980 and 1990 were used to characterise the women's neighbourhoods, defined as census tracts. Results: Cigarette smoking increased the risk of preterm delivery among both African American (OR=1.77, 95% confidence intervals (CI) (1.12 to 2.79)) and white women (OR=1.25, 95% CI (1.01 to 1.55)). However, cigarette smoking did not attenuate or modify the association of neighbourhood factors with preterm delivery. Among African American women, having public insurance modified the relation between neighbourhood unemployment and preterm delivery; among women without public insurance, the risk of preterm delivery was low in areas with low unemployment and high in areas with high unemployment, while among women with public insurance the risk of preterm delivery was highest at low levels of neighbourhood unemployment. Conclusions: Cigarette smoking was associated with preterm delivery, especially among African Americans. Adverse neighbourhood conditions had an influence on preterm delivery beyond that of cigarette smoking. The effects of some neighbourhood characteristics were different depending on individual socioeconomic status. Examining socioeconomic and behavioural/biological risk factors together may increase understanding of the complex causes of preterm delivery.